Flavonol glycoside complanatoside A requires FOXO/DAF-16, NRF2/SKN-1, and HSF-1 to improve stress resistances and extend the life span of Caenorhabditis elegans - Lin Tan; Lin Tan; Zhuo-Ya Zheng; Lv Huang; Zhong Jin; Su-Lian Li; Gui-Sheng Wu; Gui-Sheng Wu; Gui-Sheng Wu; Huai-Rong Luo; Huai-Rong Luo; Huai-Rong Luo (Frontiers Media S.A., 2022)
Aging is associated with the increased risk of most age-related diseases in humans. Complanatoside A (CA) is a flavonoid compound isolated from the herbal medicine Semen Astragali Complanati. CA was reported to have potential anti-inflammatory and anti-oxidative activities. In this study, we investigated whether CA could increase the stress resistance capability and life span of Caenorhabditis elegans. Our results showed that CA could extend the longevity of C. elegans in a dosage-dependent manner, while 50 μM of CA has the best effect and increased the life span of C. elegans by about 16.87%. CA also improved the physiological functions in aging worms, such as enhanced locomotor capacity, and reduced the accumulation of the aging pigment. CA could also reduce the accumulation of toxic proteins (α-synuclein and β-amyloid) and delay the onset of neurodegenerative disorders, such as Alzheimer's disease and Parkinson's disease, in models of C. elegans. Further investigation has revealed that CA requires DAF-16/FOXO, SKN-1, and HSF-1 to extend the life span of C. elegans. CA could increase the antioxidation and detoxification activities regulated by transcription factor SKN-1 and the heat resistance by activating HSF-1 that mediated the expression of the chaperone heat shock proteins. Our results suggest that CA is a potential antiaging agent worth further research for its pharmacological mechanism and development for pharmaceutical applications.